The Chinese Mahayana Buddhist community in Kuala Lumpur and Selangor - Mohd Nor, Nur Suriya (IIUM Press, International Islamic University Malaysia, 2018)
This study offers an observation on contemporary Chinese Mahayana Buddhist community in Kuala Lumpur and Selangor, Malaysia. The author focuses on the contemporary Chinese Mahayana Buddhist community in Malaysia as represented by the three selected Chinese Mahayana Buddhist temples in Jalan Kelang Lama of Kuala Lumpur, and Shah Alam and Ampang of Selangor. The methodology that is employed in this research is qualitative methodology that includes interviews and non-participant observation on the members of Malaysian Chinese Mahayana Buddhist temples and organizations in Kuala Lumpur and Selangor. Although generalization cannot be made to other Buddhist associations outside Shah Alam and Kuala Lumpur, findings indicate that the Malaysian Chinese Mahayana Buddhist is an organized association and there are many programs and activities offered to its members.